CBPR WITH OLDER ADULTS: EXPLORING AGE FRIENDLINESS OF SEVERAL GREATER BOSTON COMMUNITIES. (16th November 2018) - Mason, H; Gonzales, E
Abstract: Objectives. To explore elements of age-friendly communities by employing community based participatory action research (CBPR) and Photovoice with older adults. Methods. This study used CBPR and Photovoice to engage older adults in the research process which analyzed assets and barriers in their communities through a six-session class. Photovoice is an empowering process that increase sense of self of control, involvement in decision-making and critical awareness of issues (Blair & Minkler, 2009). The team evaluated journaling, picture taking, and focused group discussions on age-friendly communities. Results. Participants took a total of 115 photos. Seventy-two of the pictures documented outdoor spaces and buildings focusing on the need for safe crosswalks and sidewalks. Transportation was also highlighted expressing the need for benches with coverings at bus stops. An exhibit was held to share the findings to policy makers, community members, healthcare professionals, and friends and family. Participants finalized twenty-two Photovoice pieces for the exhibit. Of these, 63% had to do with infrastructure and 37% documented housing, respect and social inclusion, and communication and information. The photos were a novel way for policymakers and community members to connect and engage in conversations and yielded a policymaker originally uninterested in AFC becoming engaged. Discussion. Using Photovoice helps engage residents and policymakers to better understand the immediate needs of community members. To our knowledge, this was the first time Photovoice has been used in Age Friendly Community research in the United States.